Tinjauan Amal dalam Bakti Sosial Panti Asuhan Aisyiyah Kota Sungai Penuh - Fitri Handayani (Fakultas Ushuluddin, Adab, dan Dakwah, 2022)
Social service can be a community service activity between students and lecturers to build a spirit of solidarity and a high sense of morality. The community service activities carried out by Da'wah Management students are social services at the Aisyiyah Orphanage in Sungai Penuh City with the distribution of stationery for the orphans. It aims to increase students' awareness of the surrounding environment and the successful implementation of the activity was carried out on Thursday 23rd at 10.00. The target of the social service that will be carried out focuses on the Orphans and Orphans in the orphanage. The existence of community drawing activities in the form of social service is expected to provide inspiration and motivation to students, especially the general public, to share and care for each other.